Experimental research on charge determination and accumulator behavior in trans-critical CO2 mobile air-conditioning system. (15th September 2019) - Wang, Dandong; Zhang, Zhenyu; Yu, Binbin; Wang, Xinnan; Shi, Junye; Chen, Jiangping
Abstract: Natural refrigerant CO2 (R744) is one of next generation refrigerants in mobile air conditioner (MAC) application with superior environmental and heating performance. This paper investigated the charge characteristics and refrigerant migration behavior of a trans-critical CO2 MAC. A novel visualized accumulator with five observation mirrors was adopted to set up this CO2 MAC. A series of steady-state system experiments were carried out in a calorimeter facility to reveal the effects of refrigerant charge and EXV opening on system performance and accumulator behavior. In addition, the transient migration behavior of refrigerant during shutdown and start-up and the flow behavior of lubricant oil with 0.5 mm oil return hole were studied experimentally. It is found that a plateau region with optimal system performance occurred between 1100 g and 1600 g refrigerant charge. When the return hole becomes small, stratification of lubricant oil and liquid refrigerant was found in the accumulator. Highlights: The refrigerant migration behavior under different charge and EXV conditions was distinguished. A plateau region between 1100 g and 1600 g charge with optimal system performance was determined. The criteria for determining the starting and ending points of plateau region are proposed. Unnecessary liquid refrigerant evaporation during start-up may bring rapid transient response. Lubricant oil was stratified in the accumulator when the diameter of oil return hole was 0.5 mm.